"I feel and think, therefore I am": An Affect-Cognitive Theory of management decisions. Issue 2 (April 2020) - Cristofaro, Matteo
Abstract: I propose an Affect-Cognitive Theory to comprehensively understand how decisions occur in organizations. To this aim, I first review the assumptions of sensemaking and decision-making streams of research, especially the influence of bounded rationality, affective states and their relationships with cognition; then, I integrate them on the common basis of socially situated cognition. This new theory emphasizes the role of affective states in determining/being determined by cognition and its errors, pointing out decision makers' affect as the result of multi-level adaptations to the physical and social environment. Management decisions are path dependent but not immutable; they, indeed, bank on the predominant feeling resulting from the modifying interactions and regulations of decision makers with their physical and social environment. Here, decision makers are proposed as "emotional cognizers" overcoming the thinking-feeling dichotomy that has often featured in the study of management decisions. This theory is beneficial for behavioral strategy, offering the needed assumptions to intertwine human cognition, emotions, and social behavior. Highlights: This work proposes an Affect-Cognitive Theory of management decisions. Sensemaking and decision making streams of research were integrated. Affective states determine/are determined by cognition and its errors. Management decisions bank on the predominant affective state. Behavioral strategy's assumptions needed to intertwine human cognition, emotions, and social behavior are offered.